2004
DOI: 10.1002/lapl.200310094
|View full text |Cite
|
Sign up to set email alerts
|

Correct investigation of the statistic irregularities of integrated optical waveguides with the use of the waveguide light scattering

Abstract: The phenomenon of the waveguide mode scattering in the irregular planar optical waveguide is investigated. The solution of the direct problem is fined with the help of the theory of perturbations. The inverse waveguide scattering problem consists in restoring of autocovariance function and determination of irregularities' parameters by the measuring data of scattering diagram in the far zone. The computer simulation allow approving, that our method permits to receive an approximate correct solution of the inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In the general case, the irregularities can be either roughness of the interfaces of waveguide media or heterogeneities of the waveguide layer [1][2][3][4][5][6][7][8][9]. Rigorous solution of the inverse problem of the theory of waveguide scattering in an integrated optical waveguide is beyond the scope of this paper and will be given in one of our future publications (see, e.g., [13,14]). Indeed, the inverse problem of waveguide scattering is ill-posed [1-5, 10, 11].…”
Section: Analysis Of the Obtained Formula For The Green's Function Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general case, the irregularities can be either roughness of the interfaces of waveguide media or heterogeneities of the waveguide layer [1][2][3][4][5][6][7][8][9]. Rigorous solution of the inverse problem of the theory of waveguide scattering in an integrated optical waveguide is beyond the scope of this paper and will be given in one of our future publications (see, e.g., [13,14]). Indeed, the inverse problem of waveguide scattering is ill-posed [1-5, 10, 11].…”
Section: Analysis Of the Obtained Formula For The Green's Function Tmentioning
confidence: 99%
“…Our solution implies the use of a complex algorithm of retrieval of the autocorrelation function of irregularities, which is based on a combination of the classical regularization and quasi-optimal filtering. An approximate correct solution of the inverse problem of waveguide light scattering can be obtained in the class of analytic functions [13].…”
Section: Analysis Of the Obtained Formula For The Green's Function Tmentioning
confidence: 99%
“…A more detailed analysis of an inverse waveguide scattering problem and these quasi-stationary effects (due to the director motion) are beyond the scope of this work (see e.g. [6][7][8][9][10][11]).…”
Section: Zhurnal Radioelektroniki -Journal Of Radio Electronicsmentioning
confidence: 99%
“…To improve the obtained results, especially when irregularities change from small-scale (≈ 0.1-10 μm) to large-scale (≈ 20-100 μm), one need to use in the numeric analysis the analytic solutions of the problem of waveguide propagation, diffraction and scattering of electromagnetic monochromatic radiation in 3D-irregular and smoothly-irregular waveguides and waveguiding structures [7][8][9][10][11][14][15][16][17][18][19][20][21][22][23].…”
Section: Zhurnal Radioelektroniki -Journal Of Radio Electronicsmentioning
confidence: 99%
“…Although side-scattering properties of optical fibers and optical slab waveguides have been studied and corresponding experiments have been done, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] such studies of multilayer waveguide memories are seldom reported. We investigate this problem by building a simplified model.…”
Section: The Model Representationmentioning
confidence: 99%